The potential of retinoic acid receptors as prognostic biomarkers and therapeutic targets in gastric cancer - Garattini, Silvio Ken; Basile, Debora; De Re, Valli’; Brisotto, Giulia; Miolo, Gianmaria; Canzonieri, Vincenzo; Aprile, Giuseppe; Corvaja, Carla; Buriolla, Silvia; Garattini, Enrico; Puglisi, Fabio (Frontiers in Oncology, 2024)
Background: Gastric cancer is a heterogeneous collection of tumors characterized by low survival rates. All-trans retinoic acid (retinoic-acid) is a clinically useful therapeutic agent belonging to the chemical family of retinoids, which consists of both natural and synthetic derivatives of vitamin-A. Retinoids are essential components of the normal diet and they regulate different physiological processes. From a therapeutic point of view, retinoic-acid is the first example of clinically useful differentiating agent. Indeed, the differentiating properties of this compound have promoted the use of retinoic-acid as a standard of care in Acute-Promyelocytic-Leukemia, a rare form of acute myeloid leukemia. In this study, we determine the RNA expression of the six isoforms of Retinoic-Acid-Receptors (RARα/RARβ/RARγ/RXRα/RXRβ/RXRγ) in view of their potential use as gastric cancer progression markers and/or therapeutic targets. In addition, we evaluate associations between the expression of these receptors and a simplified molecular classification of stomach tumors as well as the clinical characteristics of the cohort of patients analyzed. Finally, we define the prognostic value of the various Retinoic-Acid-Receptors in gastric cancer. Methods: In this single institution and retrospective RAR-GASTRIC study, we consider 55 consecutive gastric cancer patients. We extract total RNA from the pathological specimens and we perform a NanoString Assay using a customized panel of genes. This allows us to determine the expression levels of the RAR and RXR mRNAs as well as other transcripts of interest. Results: Our data demonstrate ubiquitous expression of the RAR and RXR mRNAs in gastric cancers. High levels of RARα, RARβ, RXRα and RXRβ show a significant association with stage IV tumors, "de novo" metastatic disease, microsatellite-stable-status, epithelial-to-mesenchymal-transition, as well as PIK3CA and TP53 expression. Finally, we observe a worse overall-survival in gastric cancer patients characterized by high RARα/RARβ/RARγ/RXRβ mRNA levels. Conclusions: In gastric cancer, high expression levels of RARα/RARβ/RARγ/RXRβ transcripts are associated with poor clinical and molecular characteristics as well as with reduced overall-survival. Our data are consistent with the idea that RARα, RARβ, RARγ and RXRβ represent potential prognostic markers and therapeutic targets of gastric cancer.